Effects of different natural antioxidants on tackiness and shear strength properties in natural rubber cup lump blended with EPDM rubber as sealant: article - Rosli, Ahmad Fikri; Sharudin, Rahida Wati; Mohamed, Rahmah (2019)
Sealant based on polymer is normally used in our industry but in term of environmental friendly, there is much better raw material that can be used which is natural rubber and natural rubber (NR) cup lump is much cheaper in our industry. In term of physical properties and weathering resistance, blending with Ethylene Propylene Diene Monomers (EPDM) and antioxidants is believed to increase it physical properties and weathering resistances. The method to produce the sealant sample, the NR and EPDM will be dissolved into solution and blended together with adding the antioxidants which is curcumin and mangosteen, Methyl Ethyl Ketone Peroxide (MEKP) as curing agent and phenolic resin to improve tackiness of the sealant sample. The formulation for the sample is the same for the ratio of NR and EPDM which is 80 : 20, MEKP and phenolic resin used 5% from the total mass of sample but it is different for antioxidants where 0.5% and 1% from the total mass will be used. From the results obtained, it can says that sealant blended with natural rubber and EPDM can help in increases the physical properties but not in term of tackiness and the antioxidants that is good is curcumin and not mangosteen.